Economic vulnerability and farm-size inequality in the Cauvery Delta: A multidimensional quantitative assessment - Sudharsan, A; Velusamy, R; Balasubramaniam, P; Nirmala, D M; Anjugam, M; Prabakaran, K (Plant Science Today, 2026)
The Cauvery Delta of Tamil Nadu is experiencing accelerating agrarian stress, characterised by rising input costs, groundwater dependence and deepening indebtedness among paddy cultivators. This study assesses economic vulnerability and farm-size inequality using a mixed-methods, explanatory sequential design in 3 delta districts (Thanjavur, Tiruvarur and Nagapattinam). A stratified multi-stage sample of 450 farmers (marginal n=178; small n=197; medium n=63; large n=12) was surveyed using a pre-tested structured questionnaire, corroborated with land passbooks, input bills and focus group discussions. Quantitative analyses comprised descriptive statistics, one-way analysis of variance (ANOVA) with Tukey’s HSD, construction of a composite economic vulnerability index (CEVI) using min–max standardisation and estimation of a farm size economic stress model (FSESM) using multiple regression; qualitative data were thematically analysed to contextualise trends. Results reveal pronounced stratification: marginal farmers show the highest debt–asset ratio (3.47) and input cost intensity (≈29 % higher per ha than large farms), with net returns per hectare (₹17644) markedly below medium (₹33304) and large (₹45830) categories (all group differences p<0.001). The CEVI scores decline with farm size (marginal 0.78; small 0.62; medium 0.41; large 0.22), indicating severe vulnerability among the smallest holders. The FSESM explains 62 % of observed income variability (R² = 0.62); standardised β weights identify farm size (β = 0.61, p<0.001), irrigation reliability (β = 0.42, p<0.01), formal credit access (β = 0.38, p<0.01) and mechanisation (β = 0.29, p<0.05) as key determinants. Qualitative evidence underscores the role of informal credit dependence, tail-end irrigation delays and market access asymmetries in perpetuating risk. The findings indicate that structural factors-not farmer inefficiency-drive economic vulnerability and support a smallholder-first resilience agenda. Recommended measures include targeted low-interest/no-collateral credit, community machinery banks, strengthened tail-end irrigation governance and market and storage interventions (such as village procurement centres and stronger farmer producer organisations (FPOs)) to redress inequality and improve adaptive capacity in the Cauvery Delta.